Highly Luminescent Nucleoside-Based N, P-Doped Carbon Dots for Sensitive Detection of Ions and Bioimaging - Wang, Mengru; Liu, Mengling; Nong, Shuli; Song, Wenzhu; Zhang, Xianpeng; Shen, Shuang; Jian, Guohong; Chen, Xiangyao; Li, Zhanchao; Xu, Li (Frontiers in Chemistry, 2022)
The efficient detection of Fe3+ and MnO4− in water environment was very important and challenging due to their harmful effects on the health of humanity and environmental systems. Good biocompatibility, sensitivity, and selectivity, and superior photophysical properties, were important attributes of carbon dots-based (CDs) sensors for sensing applications. In this work, we synthesized N, P-co-doped carbon dots (N/P CDs) with guanosine 5'-monophosphate (GMP) as a green carbon source, with high fluorescence quantum yield in water (QY, 53.72%). Firstly, the luminescent N/P CDs showed a three-state “on-off-on” fluorescence response upon the sequential addition of Fe3+ and F−, with a low detection limit of 12 nM for Fe3+ and 8.5 nM for F−, respectively. Secondly, the N/P CDs also exhibited desirable selectivity and sensitivity for toxic MnO4− detection with the limit of detection of 18.2 nM, through a turn-off mechanism. Moreover, the luminescent N/P CDs successfully monitored the aforementioned ions in environmental water sample and in Escherichia coli.